A Short History of Economic Thought - Sandelin, Bo (Taylor & Francis Group, 2023)
Now in its fourth edition, A Short History of Economic Thought provides an elementary overview of the history of economic thought.The book has been thoroughly updated throughout in order to reflect changes in the landscape of the field. It continues to be a much-needed text for all introductory economics courses in the field